Determinants of tax avoidance with independent commissioners as a moderating variable - Zuhri, Fitra Wansyah; Kusuma Hasbullah, Iman Indrafana (Educoretax, 2026)
This study aims to determine the effect of leverage and transfer pricing on tax avoidance with independent commissioners as a moderating variable in mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling method used was purposive sampling. A total of 95 samples were observed over a period of five years, consisting of 19 companies. The data analysis technique used in this study was moderation analysis using moderated regression analysis. The results of this study indicate that leverage and transfer pricing do not affect tax avoidance, and independent commissioners are unable to moderate the effect of leverage on tax avoidance. In addition, independent commissioners are able to moderate and strengthen the effect of transfer pricing on tax avoidance.